Quantum-mechanical model of ion thruster for small spacecraft - V. V. Fedyanin; V. V. Shalay; V. K. Fedorov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The article presents a quantum mechanical model of an ion thruster. The basic equations describing the shape of the accelerated beam are considered. Detector plates demonstrating the interference pattern in thin films are presented. A mathematical description of the relief of thin films is given using the resulting wave function. The operation of a low-power ion engine is demonstrated. The results of numerical solution of the model with different initial values are shown. Based on the results of calculations, diagrams of the trajectories of charged particles are constructed.